Exploring the anti-site disorder and oxygen vacancies in Sr2FeMoO6 thin films - Saloaro Minnamari; Liedke Maciej Oskar; Angervo Ilari; Butterling Maik; Hirschmann Eric; Wagner Andreas; Huhtinen Hannu; Paturi Petriina (Elsevier B.V., 2022)
Abstract
To address the importance of nanoscale defects in complex magnetic oxides, we present an effective tool, variable energy positron annihilation spectroscopy, for probing the relatively small changes in anti-site disorder and oxygen vacancies of the in situ annealed double perovskite Sr
FeMoO thin films. By controlling the annealing conditions in wide pressure and temperature ranges and thus affecting the amount of nanoscale defects, we show that the magnetic properties of SrFeMoO thin films can be modified, particularly with the oxygen nonstoichiometry, and hence their spintronic functionality can be improved. On the basis of our findings together with proposed mechanism, we suggest that the annealing treatments can also be scaled to other complex magnetic perovskites to engineer nanoscale defects and thus improve their usability in future spintronic applications.